Architectural qualities of classrooms and their relation with creative ideation - Elizondo, Andrea Mariel (Universidad de Boyacá, 2019)
People can be creative to a greater or lesser extent, nevertheless, this creative potential is conditioned by the environment. Therefore, it is essential to provide adequate environments in order to encourage the development of creative thinking. The empiric study this article stem from aimed to identify functional and environmental qualities that are required to facilitate the creative process in Architecture students. In researching, students from the Universidad Autónoma de Nuevo León’s Faculty of Architecture (Mexico) assessed various classrooms taking into account the degree of ease or difficulty to carry out activities related to such discipline and generate creative ideas there. The results show correlations between the capability of fostering creativity and conditions such as height, color, sound, lighting and temperature.